Characteristics of Dynamic Response of Suspension Hydraulic Motor - Regenerative Shock Absorber (HMRSA) - Anuar, Kaspul; Guntur, Harus Laksana (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
Translational motion that happens in the vehicle's suspension due to unevenness of the road surface can be used as a source of electrical energy. A suspension that can convert translational motion into electrical energy is known as regenerative type suspension. To know the characteristics of the dynamic response, such as electrical energy potential and driving coziness which resulted by a suspension system, we need to examine the suspension. In this study, a test will be conducted to a suspension system that has been designed by researchers and was named Hydraulic Motor - Regenerative Shock Absorber (HMRSA). The test will be conducted statically and dynamically. The goal of the static testing is to obtain the spring's constant value and the damping's constant value of HMRSA. In the dynamic testing, excitation was given in the form of periodic and impulse. Periodic excitations are varied between these several frequencies such as 1.4Hz, 1.75 Hz and 2 Hz. Instead of variant of frequencies, electrical resistivity loads are varies in periodic excitations with each resistive loads such as 6 ohm, 12 ohm and 18 ohm. From dynamic testing, the electricity power values and sprung's mass acceleration which resulted by HMRSA suspension system on each frequency and electrical resistivity will be obtained. The sprung's mass acceleration value will be fundamental on how to analyze driving coziness that produced by HMRSA suspension system.